Examining the Role of Foreign Direct Investment (FDI) in Sustainable Development - Camelia Oliveira; Rifaldo Santos (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2024)
Abstract: Foreign Direct Investment (FDI) plays a pivotal role in the economic development of many countries, especially in emerging markets. This paper explores the relationship between FDI and sustainable development goals (SDGs), with a focus on sectors like renewable energy, infrastructure, and education. By analyzing case studies from Latin America and Asia, the study highlights the contributions of FDI to sustainable development, such as job creation, technology transfer, and economic growth. Additionally, it examines the limitations, including dependency risks and environmental challenges. Findings suggest that targeted FDI policies are essential for maximizing FDI's positive impacts on sustainable growth.